Étalonnage du test des cinq mots dans une population tunisienne de sujets sains - Bouattour, Nadia (Pan Afr Med J, 2019)
INTRODUCTION: Five-word test (5WT) is a memory test to assess the verbal episodic memory. It measures the memory of subjects with memory impairment, in particular within the framework of the diagnosis of Alzheimer’s disease, where it is sensitive and specific. The purpose of our study was to evaluate the effect of different sociodemographic parameters on subject’s performance, to set standards relevant to Tunisian population and to compare our results to previous studies. METHODS: We report 5WT calibration in 315 normal subjects aged 40 to 90 years (169 men, 146 women), divided into four age groups (40-49,50-59,60-69 and 70 years) having three levels of education (I: primary, II:secondary and III:higher). We calculated the mean score (standard deviation) for the different scores: Total Score (TS), Total Weighted Score (TWS), Delayed Free Recall (DFR), Total Delayed Recall (TDR) and Total Free Recall (TFR). RESULTS: The average age of subjects was 57.29 years (11.02). Performances appeared to be better in youngest and better educated subjects, without any significant difference between the two sexes. Standards were calculated on the basis of age and levels of education. CONCLUSION: Five-word test allows rapid screening of patients in whom complementary neuropsychological assessment is essential for the diagnosis of cognitive disorders.